2022
DOI: 10.1177/23813377221114283
|View full text |Cite
|
Sign up to set email alerts
|

Between Hip Hop and Me: Podcast Process Texts as Tools of Cultural Brokerage for Community Cultural Wealth

Abstract: This research features a discourse analysis of two podcasts: the “Mobb Deep, Shook Ones, Pt. II” episode of Song Exploder and the “Rap on Trial” episode of Hidden Brain. We selected these podcasts through an abductive method of what we call “fortuitous listening” because of how they reveal community cultural wealth (CCW) through their descriptions of the creative process. Specifically, our study addressed two questions: (1) What does an examination of two Hip Hop podcast process texts reveal about CCW? (2) How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Given this experience, youth actively used their song and podcast episode to own their narrative, where their rhymes and interviews attempted to offer advice and share their story for those that needed it. Prior literature suggests that hip hop podcasts are “process texts” that allow artists to illustrate how their stories transcend entertainment and are intimately connected to their culture, identity, and community (Griffith, 2021; Griffith et al, 2022). Relatedly, various studies have explored the use of hip hop cultural processes like lyric writing, mixtape making, dancing, and studio construction as group work processes for students to explore their stories (Levy, 2019; Levy & Adjapong, 2020; Levy & Wong, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this experience, youth actively used their song and podcast episode to own their narrative, where their rhymes and interviews attempted to offer advice and share their story for those that needed it. Prior literature suggests that hip hop podcasts are “process texts” that allow artists to illustrate how their stories transcend entertainment and are intimately connected to their culture, identity, and community (Griffith, 2021; Griffith et al, 2022). Relatedly, various studies have explored the use of hip hop cultural processes like lyric writing, mixtape making, dancing, and studio construction as group work processes for students to explore their stories (Levy, 2019; Levy & Adjapong, 2020; Levy & Wong, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of leveraging youth culture in the elevation of practices (Rawls & Petchauer, 2023), podcasting has entered popular discourse over the last decade, by way of hip hop artists and journalists creating their own shows (Griffith et al, 2022). Podcasting has been successfully used in educational settings where students learn to improve their communication skills, collaborate with their peers, and gain confidence in their work (Besser et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to most, but not all, studies of hip-hop pedagogy ( Kruse, 2014 ; Buffington and Day, 2018 ; Adjapong, 2021 ; Brown, 2021 ; Wheatley, 2022 ), we found that the key element hip-hop is used to define hip-hop pedagogy ( Anyiwo et al, 2022 ; Griffith et al, 2022 ; Guanci, 2022 ; Uca et al, 2022 ) in the following ways:…”
Section: Methodsmentioning
confidence: 97%